PENGARUH PENGUMUMAN BOND RATING VERSI PT PEFINDO TERHADAP ABNORMAL RETURN SAHAM PERUSAHAAN DI BURSA EFEK JAKARTA - Warsito Kawedar; - Suwanti (Universitas Wahid Hasyim, 2009)
Bond rating is one of information which needed by investors. This information shows capability bondholders in paying their liability and interest expense. This research will examine whether bond rating will effect abnormal return with windows event 5 days before and after published of bond rating. This research was conducted at Jakarta Stock Exchange (JSX) using 31 emitens as samples. Data of bond rating use rating version PT Pefindo. Abnormal return was counted with market adjusted model. The hypothesis examined with T-Test. The result of hypothesis analysis shows significant. It shows that there is difference abnormal return before and after announcement of bond rating. Announcement of bond rating is god news. Keywords: abnormal return, bond rating, and market adjusted model.